Due Case dei bambini di Aurelio Galfetti, 1960-1966 - Nicola Navone (ArchAlp)
At the beginning of his professional career, Aurelio Galfetti designed and built two kindergartens, or Children Houses (as they were then called in Ticino), in his hometown of Biasca (in collaboration with Ivo Trümpy) and in a nearby village, Ludiano (with Flora Ruchat-Roncati and Ivo Trümpy). In both cases, Galfetti refrains from referencing Alpine imagery, instead drawing inspiration from the works of Le Corbusier and Alvar Aalto. Galfetti does not approach these influences out of a fleeting fascination, but instead identifies in the works of these artists appropriate responses to the specific context and function of these two projects. In both instances, the models are not drawn from the field of school architecture but reinterpret buildings imbued with a sense of domesticity. This approach aligns not only with the implicit connection to the Montessori concept of these Children Houses, but also with the Modernist idea of “home”, cultivated with clear pedagogical intent.